(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this paper, we analyze the notion of interculturality through the epistemic asymmetries between indigenous and school knowledge. The analysis considers a critical perspective of the concept of interculturality and an indigenous epistemic-pedagogical approach for the development of intercultural educational knowledge, based on social and cultural aspects. We argue that the school system denies the epistemic rationalities supported by the indigenous knowledge system and hinders intercultural articulation when only the own cultural aspects are emphasized. Finally, we conclude that the challenge for critical interculturality, in indigenous context, is structural-epistemological.